Gen-Z dan Minat Beli Kosmetik di e-Commerce - Oktavia, Dini; Ferawati, Rofiqoh (Manajemen Keuangan Syariah, 2025)
The purpose of this study was to determine the effect of digital marketing, halal labeling and celebrity endorsersement on the interest in buying cosmetics in generation z in Jambi province. The method used is a quantitative method, using the SPSS application. This study used 100 samples of generation z spread across Jambi province. The findings of this study are that digital marketing has a significant effect on buying interest, amounting to 0.004 <0.05. Halal labeling does not have a significant effect on buying interest, with a significant value of 0.866> 0.05. Celebrity endorsement has a significant effect on buying interest, with a significant value of 0.000 <0.05. Digital Marketing, Halal Labeling and Celebrity Endorsersement together have a significant effect on purchasing interest, with an Adjusted R square value (coefficient of determination) of 0.453 or 45.3%. This shows that the influence of the variables digital marketing (X1), halal labeling (X2), and celebrity endorsement (X3) is 45.3% and the remaining 54.7% is influenced by other variables not included in this model. Keywords: Digital marketing, Halal, Endorsement, Celebrity, Purchasing Interest, Gen-Z